Aristotle and the automation of logic. A reading from artificial intelligence - Vargas Guillén, Germán (Estudios de Filosofía, 2001)
This lecture proposes an alternative approach to the relationship between syntax and semantics in Artificial Intelligence. First, the problem of automatizing the contents is considered from the point of view of the opposition syntax-semantics. Then it is explained how syntax can be reduced to the transformation of Logic of Terms into Logic of Propositions. Attention is also devoted to the fact that Semantics is basically a matter of correlation, as viewed from the phenome nological perspective. Finally, it is showed that there are in Artificial Intelligence different levels of representation of intentionality, both in the psychological and epistemic sense.